Effects of G-CSF on hPDLSC proliferation and osteogenic differentiation in the LPS-induced inflammatory microenvironment - Hui Yu; Pengcheng Wang; Haibin Lu; Jiurong Guan; Fang Yao; Tianyi Zhang; Qiuxu Wang; Zuomin Wang (BMC, 2023)
Abstract Background Periodontitis is a chronic infectious disease of periodontal support tissue caused by microorganisms in dental plaque, which causes alveolar bone resorption and tooth loss. Periodontitis treatment goals include prevention of alveolar bone resorption and promotion of periodontal regeneration. We previously found that granulocyte colony-stimulating factor (G-CSF) was involved in periodontitis-related alveolar bone resorption through induction of an immune response and subsequent destruction of periodontal tissue. However, the mechanisms underlying the effects of G-CSF on abnormal bone remodeling have not yet been fully elucidated. Human periodontal ligament stem cells (hPDLSCs) are major modulators of osteogenic differentiation in periodontal tissues. Thus, the aim of this study was to investigated whether G-CSF acts effects on hPDLSC proliferation and osteogenic differentiation, as well as periodontal tissue repair. Methods hPDLSCs were cultured and identified by short tandem repeat analysis. The expression patterns and locations of G-CSF receptor (G-CSFR) on hPDLSCs were detected by immunofluorescence analysis. The effects of G-CSF on hPDLSCs in a lipopolysaccharide (LPS)-induced inflammatory microenvironment were investigated. Specifically, Cell-Counting Kit 8 (CCK8) and Alizarin red staining were used to examine hPDLSC proliferation and osteogenic differentiation; reverse transcription-polymerase chain reaction was performed to detect the expression patterns of osteogenesis-related genes (alkaline phosphatase [ALP], runt-related transcription factor 2 [Runx2], and osteocalcin [OCN]) in hPDLSCs; and Western blotting was used to detect the expression patterns of phosphatidylinositol 3-kinase (PI3K) and protein kinase B (Akt) of PI3K/Akt signaling pathway. Results hPDLSCs exhibited a typical spindle-shaped morphology and good clonogenic ability. G-CSFR was mostly localized on the cell surface membrane. Analyses showed that G-CSF inhibited hPDLSC proliferation. Also, in the LPS-induced inflammatory microenvironment, G-CSF inhibited hPDLSC osteogenic differentiation and reduced the expression levels of osteogenesis-related genes. G-CSF increased the protein expression levels of hPDLSC pathway components p-PI3K and p-Akt. Conclusions We found that G-CSFR was expressed on hPDLSCs. Furthermore, G-CSF inhibited hPDLSC osteogenic differentiation in vitro in the LPS-induced inflammatory microenvironment.